A new species of Thamnodynastes Wagler, 1830 from western Amazonia, with notes on morphology for members of the Thamnodynastes pallidus group (Serpentes, Dipsadidae, Tachymenini) - Trevine, Vivian C.; Caicedo-Portilla, José Rancés; Hoogmoed, Marinus; Thomas, Robert A.; Franco, Francisco L.; Montingelli, Giovanna G.; Osorno-Muñoz, Mariela; Zaher, Hussam (Zootaxa, 2021)
The genus Thamnodynastes is the most diverse within the tribe Tachymenini, with an extensive and complex taxonomic history. The brief descriptions and lack of robust diagnostic characters are the main sources for identification errors and for the difficulty to assess the diversity estimates of the genus. The Thamnodynastes pallidus group was briefly designated to encompass the most arboreal species of the genus, with thinner bodies and longer tails: T. pallidus, T. longicaudus, T. sertanejo, and a fourth undescribed species. After its designation, no other paper addressed this group and its morphological variation, especially for the hemipenis, is still undetermined. After the analysis of all species of Thamnodynastes we were able to corroborate the distinctiveness of the T. pallidus group and to accurately diagnose its fourth species from the western portion of the Amazonia lowlands. The new species is distinguishable from all congeners, except T. sertanejo, by the absence of ventral longitudinal stripes, 17/17/11 dorsal scale rows, and dorsal dark brown blotches on the anterior third of the body. The new species is distinguished from T. sertanejo by the higher number of subcaudals, lower number of ventrals, and smaller body and head sizes. We also provide additional diagnostic features for the Thamnodynastes pallidus group, including new data on hemipenial variation. Finally, we briefly discuss the defensive behavior and morphological characters associated with arboreality in members of the T. pallidus species group.